HUBUNGAN CITRA TUBUH, AKTIVITAS FISIK, DAN PENGETAHUAN GIZI SEIMBANG DENGAN STATUS GIZI REMAJA PUTRI - Hepti Muliyati (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
The results of Nutrient State Monitoring 2018, mentioned that obesity and emaciation among girls aged 12-18 decreased from 38,5% to 19,4% in obesity, and 6,7% to 4,7% in emaciation. Both Poor nutrient and over nutrition in Indonesia still occur in adolescenceespecially in young women. There are several factors that influence nutrient status including body image, physical activity, and balanced nutrient knowledge. The aim is to analyze the relationship of body image, physical activity, and balanced nutrient State of young women in Tinangkung 1 State High School. Type of quantitative research using a Cross Sectional study design. The number of samples was 94 people and it taken by purposive sampling technigue. Data analysis using Chi-Square. The results showed that most of respondents had positive body image (52,1%), heavy physical activity (60,6%), enough nutrition knowledge (40,4%), and normal nutrient state (85,1%). Chi-Square test results between body image, physical activity, and knowledge of balanced nutrient with nutrient state obtained results each of p value 0,297; 0,000; 0,001. The conclusion was that there was no correlation between body image and nutritional status of young women, there was a relationship between physical activity and balanced nutrition knowledge with the nutritional status of young women. There fore, it is necessary to conduct the presentation of balanced nutritional state for young women in SMA Negeri 1 Tinangkung. Keywords: body image, physical activity, knowledge of balanced nutrition, nutrient state